MULTIKULTURALISME DALAM BUDAYA SENI PERTUNJUKAN TARI DI YOGYAKARTA - Pramutomo, R.M. (Institut Seni Indoensia Surakarta, 2009)
ThisÂ article will strive a kind of exploration studies arround multiculturalism and its impact to the dance and performance appearance in Yogyakarta dance tradition. Multiculturalism and its shaping have several elements which support the new kind of creative process. In the case of Yogyakarta dance tradition, it regards to the extra-tolerance sense of the aesthetic authority. Based on these evidences, this article will explore a study of traditional sources from the dance naration texts collected by the palace of Yogyakarta. In fact, it has been strongly emphased on the archi val studies and explanation process through the heuristic explanation. On the other hand, this article would like to examine a relationship between a sense of extra-tolerance inside the dance tradition itself and the creative requirement belong to the new kind ofprocess itself With an arts histori cal approach, this article presents an explorative study of the multiculturalism as ingredients which improve the development of new mainstream of creative process in the field of dance tradition fluently.Â Keywords: multiculturalism, extra-tolerance, and creative process.